Techno-Economic Analysis of Electricity Generation From Rice Husk Based On Demand For Electric Vehicle: A Case Study In Surabaya City, Indonesia - Muthia, Rahma; Putro, Muhamad Rifan Aji Wahyudi (Jurnal Rekayasa Kimia & Lingkungan, 2025)
On August 5, 2019, the President of the Republic of Indonesia issued a Presidential Regulation (Perpres) concerning the acceleration of the battery-based electric motorized vehicle program for road transportation. However, fossil energy sources such as coal, oil and natural gas used in conventional power plants are increasingly limited, so alternative energy that is more sustainable and environmentally friendly is needed. One source of sustainable electrical energy is biomass wastes such as rice husks, which have a potential CO2emission reduction of 142,610.51 tCO2/year. The method used for technical analysis by simulating the process of processing biomass waste into electrical energy using the gasification process with Aspen Plus software as a tool to obtain optimum operating conditions. Biomass with flow 32,906.9 kg/h is fed into the gasification process area and then produces 1,538 kmol/h of syngas which reacted with airflow 9,779 kmol/h. The selling target for electric products is to supply the electricity needs of electric vehicle users in Surabaya. This research is possible to do with the consideration that East Java is the province with the largest rice production in Indonesia, Surabaya is a metropolitan city and is the economic center of the province of East Java so it is possible to developments related to the infrastructure of electric vehicles and the electric vehicle itself. Based on the economic feasibility analysis, the biomass power plant has an NPV of Rp.163 million, an IRR is 15.01%, WACC 7.34%, LCOE 4.063 Rupiah/kWh and a payback period of 6 years.